Emotional Intelligence as Predictor of Work Motivation: The Mediating Role of Self-Esteem - Case of Prospective Indonesian Domestic Migrant Workers - Anwar, Anwar; Mustika, Martina Dwi (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Abstracts are written in Indonesian and English wit Through the Decree of the Minister of Manpower No. 313 of 2015 established the Indonesian National Work Competency Standards (SKKNI) for domestic workers which became the guideline for competency test material for Prospective Indonesian Domestic Migrant Workers (Ministry of Manpower, 2015). Most of those competencies are technical competencies such as Operating Cleaning Equipment, Cleaning Living Rooms and Bedrooms or Cleaning Bathrooms and Toilet Facilities, which are easily observed by the assessor with the naked eye, so we consider it necessary to find out the mental processes behind the technical activities of Prospective Indonesian Domestic Migrant Workers such as how they identify their own strengths and weaknesses, self-motivation and managing emotions that encourage work motivation. The study was non-experimental based on quantitative research and utilized a survey method to collect data. Linear regression method was used to predicts the value of the Intrinsic Motivation, which is the response or outcome Emotional Intelligence being analyzed. The hypothesis of this study is that there is a relationship between emotional intelligence and work motivation which is mediated by self-efficacy. The data collected consisted of 210 Prospective Domestic Migrant Workers. Based on the results of the Pearson correlation coefficient, it can be seen that there is significant relationship between Emotional Intelligence and Intrinsic Motivation (r (208) = 1,0; p < 0,001), partially mediated by Self-Efficacy, which is 28.1%. Thus, all Job Training Institutions for Prospective Indonesian Domestic Migrant Workers must pay more attention to developing emotional intelligence for Prospective Indonesian Domestic Migrant Workers, instead of only focusing on providing technical knowledge related to work, but also psychological provision because it has been proven that technical ability has a positive correlation with emotions in predicting work motivation.